Chemokine secretion by human polymorphonuclear granulocytes after stimulation with Mycobacterium tuberculosis and lipoarabinomannan. - Riedel, D D (1997)
Macrophages (MAC) and polymorphonuclear granulocytes (PNG) are professional phagocytes which perform essential functions in antibacterial defense. The intracellular bacterium Mycobacterium tuberculosis persists and replicates in resting macrophages. Although it is generally assumed that activated MAC are central to protection against M. tuberculosis, PNG may also contribute to defense. We wondered whether PNG produce proinflammatory chemokines after stimulation by M. tuberculosis or its major cell wall component, lipoarabinomannan (LAM). In this study, we showed that M. tuberculosis- and LAM-activated human PNG secrete the leukocyte attractant interleukin-8 (IL-8) and the PNG-specific chemokine GRO-alpha in a dose-dependent manner. Treatment of PNG with the leukotriene-B4 inhibitor MK-886 prior to stimulation with M. tuberculosis or LAM partially blocked IL-8 and GRO-alpha induction, suggesting involvement of the 5-lipoxygenase pathway in the secretion of these chemokines. We conclude that PNG contribute to early resistance to M. tuberculosis via chemokine secretion.